Web-based Sales and Purchase System for Care Technology Enterprise - Liew, Kenn Shearnn; Ramli, Sofia Najwa (Applied Information Technology And Computer Science, 2021)
Web-based Sales and Purchase System is intended to help a business company to manage its sales and purchase information. Care Technology Enterprise is a small company that sells computer products and runs a physical shop. The owner and employees had some problems in managing their sales and purchase information. The owner of the company used traditional methods to manage and store their information. The traditional methods of managing their information were very unorganized, requires a lot of space to store the information, and insecure due to physical storage. Therefore, this project aimed to design, develop, and test an online sales and purchase system for Care Technology Enterprise. The system helped them organize their sales and purchase information using computerized methods and databases. Storing information in databases makes adding, updating, and removing processes much easier while also providing security to protect the information. The system was a web-based system that provides the availability of the data. It was written in PHP programming language. The project followed the object-oriented software development methodology because the system was developed using an object-oriented approach. The database used MySQL service, and the system hosted on InfinityFree web hosting service. The system managed client, user accounts, expense, inventory, invoice, and sales information while allowing purchase orders to be recorded. The system had succeeded in achieving all the objectives set in this project.